A STRUCTURAL-SEMANTIC STUDY OF COMPOUND VERBS FORMED WITH THE AUXILIARY VERB KARDAN (“TO DO”) IN THE PERSIAN LANGUAGE - Sabohat A. Baxadirova (International Journal of Literature and Language Studies, 2026)
ABSTRACT: This article investigates the structural and semantic characteristics of compound verbs formed with the auxiliary verb kardan (“to do”), one of the most productive auxiliary verbs in contemporary Persian. The study analyzes the formation patterns of compound verbs, the morphological nature of their nominal components, the grammatical functions of the auxiliary verb, and the processes of semantic transformation involved in their formation. In addition, the syntactic valency and functional potential of these compound verbs in modern Persian are examined.